Deductive analysis for Municipalities of Baghdad city, within the healthy city program - Ali, Heyam Hameed Abdulmajeed (Journal of engineering sciences and information technology, 2024)
The city of Baghdad is constantly expanding due to its high population being the capital of Iraq. Today, more than ever, it faces serious challenges with regard to the quality of life in the urban environment, such as the conservation of water sources, waste treatment, noise, the preservation of green spaces, etc., as well as considerations directly related to the urban individual, i.e. low levels of public health, low levels of age and widespread poverty.This research presents a methodology proposal to achieve the objectives of the health city in the city of Baghdad, where it linked the achievement of the urban health system and the efficient management of municipal services to reduce pollution in the capital Baghdad and improve the health of its residents. The research reviewed the definitional concepts of the health city, its objectives and the most important tools, and also reviewed the most important previous studies in the field of health city indicators The research analyzed in the practical applied part the municipalities of the city of Baghdad under indicators that were extracted from the data of the health file of the city of Baghdad were presented to a sample of experts between architects and city planners to determine the most affected municipalities by these indicators, and reached results that identified weaknesses in the municipal service of each of these municipalities. The research followed the deductive approach to analyze the municipalities of the city of Baghdad during a specific period of time, and has reached a final conclusion that the first and second Sadr municipality indicates a wide imbalance in the services related to the health of individuals, and put his recommendations regarding the development of municipal administration to achieve the goals of the urban health system for all municipalities of Baghdad and the municipality of Sadr first and second specifically.
Keywords: Health City program; municipalities; municipal service